Faktor-Faktor yang Mempengaruhi Akuntabilitas Keuangan Masjid Studi Kasus pada Masjid di Provinsi Sulawesi Barat - Muhammad Yusran (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2021)
ABSTRACTThe financial accountability of mosques in their accounting practice is still very simple, as well as in financial reporting, so that it is far from the applicable standard provisions. The purpose of this study was to analyze the factors that affect the financial accountability of mosques in West Sulawesi Province. This study used a survey method in the study population, namely all mosques in West Sulawesi Province with incidental sampling techniques and collected as many as 109 respondents from six districts in West Sulawesi Province, then analyzed by multiple regression using SPSS. The results showed that the variables of financial management, internal control, the role of stakeholders, and financial management standards had a positive and significant influence both partially and collectively on the financial accountability variables of mosques. Meanwhile, human resource competence, the use of ICT in this study, does not have a partially significant effect on the financial accountability of mosques. However, it still has a constructive influence simultaneously with the variables of financial management, internal control, the role of stakeholders, and fund management standards on financial accountability. Researchers recommend that local governments in West Sulawesi and related stakeholders improve human resource competence and technology adaptation for mosque managers in managing finances based on the standards of PSAK 45 and PSAK 109.